PENGARUH IKLIM ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL DAN KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA KARYAWAN PADA PT PERTIWI INDOMAS SEMARANG - Waluyo Ihsan, 11.05.51.0093; Suharmanto, Toto (Students Journal of Economic and Management, 2016)
This study discusses the influence of organizational climate, leadership transformational and transactional leadership on employee performance. Places were taken on the employees who are still actively working at PT. Pertiwi Indomas Semarang. In the operations of the company there is a problem or a phenomenon that is not achieving the revenue targets that are established by the management company. A sample of 89 respondents, using purposive sampling techniques that sampling based on specified criteria or considerations include: employees who are still actively working at PT. Pertiwi Indo Mas Semarang, employees have worked at least one year; and willing to be the respondent. Methods of data analysis using linear regression. The test results showed that there are significant positive and significant correlation between organizational climate, transformational leadership and transactional leadership on employee performance.. Keywords:      organizational climate, transformational leadership, transactional leadership and employee performance.